CD47 is Up-Regulated on Leukaemia Cells to Avoid Apoptosis In Vitro - Ikenna Kingsley Uchendu, Oliver Chukwuma Orji, Chidozie Elochukwu Agu, Blessing Eluke Chekwube, Tochi Faith Nwosu (Journal of Applied Pharmaceutical Science, 2018)
Treatment failure in T-cell acute lymphoblastic leukaemia (T-ALL) occurs when leukemic blasts acquire resistance to chemotherapeutic agents. Current research efforts are focused on the search for targets for the development of more effective and less toxic anti-leukemic drugs. CD47 has been suggested to be involved in chemo resistance and cell metastasis. Although several potential mechanisms were suggested to explain the therapeutic effect of CD47-targeting; the different effects by CD47 are still not well understood. In this study, we assessed the effect of doxorubicin on CD47 expression in jurkat T cells. Jurkat cells in complete medium were cultured with doxorubicin (50-1000nM) or control for 0, 24, 48 and 72 hours. Cells were stained with anti-CD47 FITC. Flow cytometry analysis was used for measurement of fluorescence intensity. Cell viability was detected using trypan blue exclusion test. Treatment with doxorubicin modulated the up-regulation of CD47 on membrane surfaces of jurkat cells with no significant killing of the cells. leukaemia cells exert their anti-apoptotic role through increased CD47 expression. CD47 is a novel functional protein in jurkat T cells with promising therapeutic potential and may provide insight for targeted therapy against T-ALL disease.
Keywords: CD47, jurkat T cells, leukaemia, upregulation, doxorubicin, chemotherapy, apoptosis, flow cytometry.